1989
DOI: 10.1128/aem.55.12.3155-3161.1989
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of trichloroethylene by Methylosinus trichosporium OB3b

Abstract: The methanotroph Methylosinus trichosporium OB3b, a type II methanotroph, degraded trichloroethylene at rates exceeding 1.2 mmol/h per g (dry weight) following the appearance of soluble methane monooxygenase in continuous and batch cultures. Cells capable oxidizing trichloroethylene contained components of soluble methane monooxygenase as demonstrated by Western blot (immunoblot) analysis with antibodies prepared against the purified enzyme. Growth of cultures in a medium containing 0.25 microM or less copper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
176
1
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(181 citation statements)
references
References 34 publications
3
176
1
1
Order By: Relevance
“…Many such oxygenases have a very broad substrate range, and can fortuitously oxidize chloroethenes, yielding unstable chlorinated epoxides that subsequently break down spontaneously. The aerobic cometabolism of chlorinated ethenes has been studied in diverse hydrocarbon-oxidizing bacteria, including those that grow on phenol (Folsom et al, 1990), toluene (Chauhan et al, 1998), methane (Fogel et al, 1986;Tsien et al, 1989), ethene and ethane (Freedman & Herz, 1996;Koziollek et al, 1999), propane (Wackett et al, 1989;Phelps et al, 1991;Malachowsky et al, 1994), propene (Ensign et al, 1992;Saeki et al, 1999), and ammonia (Vannelli et al, 1990). Much of the relevant literature has been reviewed previously (Semprini, 2001).…”
Section: Aerobic Cometabolic Oxidation Of Chloroethenesmentioning
confidence: 99%
“…Many such oxygenases have a very broad substrate range, and can fortuitously oxidize chloroethenes, yielding unstable chlorinated epoxides that subsequently break down spontaneously. The aerobic cometabolism of chlorinated ethenes has been studied in diverse hydrocarbon-oxidizing bacteria, including those that grow on phenol (Folsom et al, 1990), toluene (Chauhan et al, 1998), methane (Fogel et al, 1986;Tsien et al, 1989), ethene and ethane (Freedman & Herz, 1996;Koziollek et al, 1999), propane (Wackett et al, 1989;Phelps et al, 1991;Malachowsky et al, 1994), propene (Ensign et al, 1992;Saeki et al, 1999), and ammonia (Vannelli et al, 1990). Much of the relevant literature has been reviewed previously (Semprini, 2001).…”
Section: Aerobic Cometabolic Oxidation Of Chloroethenesmentioning
confidence: 99%
“…In solutions which contained less than 0.015 mg Cu/L, soluble MMO production was dominant in cultures of Methylosinus trichosporium OB3b. 34 It has been shown that the soluble form of MMO is more effective in catalyzing chlorinated ethene Therefore, for use of methanotrophs in the removal of toxic contaminants from water, the type of MMO synthesized would be of great concern.…”
Section: Introductionmentioning
confidence: 99%
“…Such enzymes are produced by bacteria growing on e.g. methane [93,94], toluene [95,96], isoprene [97], p-cumene [98], propene [99], propane [100], or ammonia [101]. In many, but not all, such bacteria chlorinated ethylenes are converted co-metabolically.…”
Section: Aerobic Degradation Of Chlorinated Ethylenesmentioning
confidence: 99%
“…In Mycobacterium aurum the initial step in vinyl chloride metabolism is catalyzed by alkene monooxygenase, transforming vinyl chloride to the reactive epoxide chlorooxirane. Probably, the alkene monooxygenase is not specifically evolved for vinyl chloride degradation: co-metabolic conversion of vinyl chloride by microorganisms exhibiting monooxygenase activity is a widespread phenomenon [94,96,99,108,109], but the mycobacteria isolated by Hartmans are still the only organisms known to grow on vinyl chloride. The use of a general enzyme like alkene monooxygenase in M. aureurn [1 I0] suggests that the actual adaptation that allows this organism to grow on vinyl chloride encompasses the acquisition of an enzyme that catalyzes the subsequent conversion of the highly toxic chlorooxirane into products that can be funneled into a productive metabolic route.…”
Section: Aerobic Degradation Of Chlorinated Ethylenesmentioning
confidence: 99%